On the spatial and temporal dependence of CO2 emission on soil properties in sugarcane (Saccharum spp.) production - Moitinho, Mara Regina [UNESP]; Padovan, Milton Parron; Panosso, Alan Rodrigo [UNESP]; Teixeira, Daniel De Bortoli [UNESP]; Ferraudo, Antonio Sergio [UNESP]; La Scala, Newton [UNESP] (Elsevier B.V., 2015)
CO2 production in soil is the result of biological processes, such as the decomposition of organic matter and the respiration of roots and soil organisms. It also depends on the physical, chemical and biological properties and their interactions. Such properties exhibit variability in space and time, which provides a high degree of complexity on soil CO2 emission (FCO2). However few studies discuss the spatial and temporal component of FCO2, jointly. The objective of this study was to characterize the spatial and temporal variability of FCO2 and its relationship to the edaphoclimatic properties of the soil in sugarcane fields. The LI-8100 system, which monitors changes in CO2 concentrations within a portable chamber, was used to assess the FCO2. The CO2 flux measurements, soil temperature (0-20 cm, thermometer of LI-8100) and soil water content (0-12 cm, TDR device) were evaluated concomitantly. Overall, the mean values for FCO2, soil temperature and soil water content were 2.8 mu mol m(-2) s(-1), 19.48 degrees C and 17.20 m(3)m(-3), respectively. The FCO2 was positively correlated with the soil organic matter content (SOM) (r = 0.67, p < 0.001), the air-filled porosity (AFP) (r = 0.71, p < 0.001) and the available phosphorus (r = 0.28, p < 0.05) but negatively correlated with the soil C/N ratio (r = 0.75, p < 0.001) and soil water content (r = -0.29, p < 0.05). The air-filled porosity was the last property added to the multiple regression model and explained 77% of the spatial variability in soil CO2 emission. The largest temporal variations in CO2 emissions over the study period were explained by changes in soil water content, especially after rainfall. Spatially, the CO2 emission is modeled by chemical (organic matter and soil C/N ratio) and physical (air-filled porosity) soil properties which are associated to production and transport of CO2 in soil.
Keywords: Soil properties; Soil respiration; Soil CO2 efflux; Variability